Characteristics of Expression of Matrix Metalloproteinases (MMP-2 and MMP-9) in Glottic Squamous Cell Carcinoma and Benign Vocal Fold Lesions - Uloza, Virgilijus (Clin Exp Otorhinolaryngol, 2015)
OBJECTIVES: The aim of this study was to investigate expression profile of matrix metalloproteinases (MMP-2 and MMP-9) in glottic squamous cell carcinoma (SCC) and benign vocal fold lesions (BVFLs) and to correlate it with clinical and pathological features. METHODS: The immunohistochemical expression of MMP-2 and MMP-9 was investigated in specimens taken from 217 patients group, including vocal fold polyps (n=39), recurrent respiratory papillomatosis (n=30), laryngeal keratosis (n=36), glottic SCC (n=112), and the normal tissue of vocal fold (n=12, control group). The expression of MMP-2 and MMP-9, both in epithelium and stroma cells, was graded on a semiquantitative scale, ranging from 0 (no expression) to 18 points (high expression). RESULTS: Expressions of both, MMP-2 and MMP-9 were significantly higher in the glottic SCC group comparing with BVFL group. Significant higher expression of parenchymal MMP-2 (P<0.001) and stromal MMP-9 (P=0.01) was revealed in the group of moderate/poorly differentiated glottic SCC comparing with well differentiated glottic SCC group. Expression of stroma MMP-2 was found to be correlated with nodal metastasis (P=0.030). Expressions of both, MMP-2 and MMP-9 were not correlated with clinical stage, tumor T value, smoking, alcohol use, age in the glottic SSC patients group. The MMP-2 stroma value of 11.2 points was determined as the optimum point (limiting value) for separating BVFL and glottic SCC patient groups. CONCLUSION: Our results suggest that expressions of both MMP-2 and MMP-9 are up-regulated already in the development of BVFL, the next determinant step is concerned with occurrence of malignization. Limiting value of stroma MMP-2 demonstrates prognostic importance of MMP-2 in glottic SCC carcinogenesis.